Intercellular adhesion molecule‐1 (ICAM‐1) expression correlates with oral cancer progression and induces macrophage/cancer cell adhesion. Issue 3 (7th March 2013) - Usami, Yu; Ishida, Ken; Sato, Sunao; Kishino, Mitsunobu; Kiryu, Megumi; Ogawa, Yuzo; Okura, Masaya; Fukuda, Yasuo; Toyosawa, Satoru
<x xml:space="preserve">Abstract</x> Intercellular adhesion molecule‐1 (ICAM‐1) is a transmembrane glycoprotein in the immunoglobulin superfamily, which plays an important role in cell adhesion and signal transduction. Although ICAM‐1 is believed to play a role in several malignancies, it is still uncertain whether or not ICAM‐1 expression contributes to cancer progression. In this study, we performed clinicopathological and cell biological analyses of ICAM‐1 expression in oral squamous cell carcinoma (SCC). First, we examined the ICAM‐1 expression in tongue SCC immunohistochemically, and revealed that ICAM‐1 was expressed predominantly at the invasive front area of tongue SCC. ICAM‐1 expression at the invasive front area was correlated with invasion, lymph node metastasis and increased blood and lymphatic vessel density of the tongue SCC. The relationship between ICAM‐1 expression and clinicopathological factors were consistent with the increased proliferation, invasion and cytokine‐production activities of ICAM‐1‐transfected SCC cells. Second, we analyzed the relationship between macrophages and ICAM‐1‐expressing tongue SCC cells because ICAM‐1 is known to act as a ligand for adhesion of immune cells. Increased ICAM‐1 expression in tongue SCC was correlated with increased macrophage infiltration within SCC nests. Moreover, macrophage/SCC‐cell adhesion through ICAM‐1 molecule was revealed using an in vitro cell adhesion and blockade assay. These findings indicate that ICAM‐1 plays an important role in tongue SCC progression, which may result from the SCC‐cell activity, angiogenic activity, lymphangiogenic activity and macrophage/SCC‐cell adhesion.